Pattern of asphyxial deaths: A medicolegal study - Kumar Guntheti , Bharath (Journal of Indian Academy of Forensic Medicine, 2021)
Violent asphyxia is a commonly reported mode of death. Based on a three years retrospective study, conducted in the Dept. of Forensic Medicine, Mamata Medical College between Jan 2016 and Dec 2018, details about all violent asphyxial cases collected. During the study period 148 (7.74%) cases were reported resulting from violent asphyxia (148/100000 per year) out of 1912 medicolegal autopsies conducted. The data was collected from relatives, hospital records and autopsy reports. Incidence of asphyxial deaths is 7.74% of total autopsies. Most victims were 21–30-year-old males. The most common method amongst them was hanging 77 (52.02%) followed by drowning 28 (18.91%). In majority of the cases, the incident occurred at the residence of the victim during the day. Most cases were encountered during winter especially in November. All cases of hanging were suicidal. Homicidal hanging was not reported for any case. On the other hand, all the cases of smothering, strangulation and throttling were homicidal. Among the cases of drowning, 89.28% were accidental and 10.71% were suicidal. The prime motive behind violent asphyxial deaths was personal problems. Domestic violence plays a great role in suicidal and homicidal cases. The primary objective of the study was to analyse the epidemiological profile, seasonal variation, motive, manner, cause, circumstance, recent trends and patterns of asphyxial deaths as well as the preventive measures.